2001
DOI: 10.1128/iai.69.5.2894-2901.2001
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhi Possesses a Unique Repertoire of Fimbrial Gene Sequences

Abstract: Salmonella enterica serotype Typhi differs from nontyphoidal Salmonella serotypes by its strict host adaptation to humans and higher primates. Since fimbriae have been implicated in host adaptation, we investigated whether the serotype Typhi genome contains fimbrial operons which are unique to this pathogen or restricted to typhoidal Salmonella serotypes. This study established for the first time the total number of fimbrial operons present in an individual Salmonella serotype. The serotype Typhi CT18 genome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
192
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(199 citation statements)
references
References 50 publications
(62 reference statements)
4
192
0
Order By: Relevance
“…In ®ve cases the operons are¯anked by genes encoding transposases or integrases, again implying horizontal acquisition. Such high redundancy of ®mbria-related genes is also found in other bacterial pathogens, including Escherichia coli and Salmonella enterica serovar Typhi 17 . A large arsenal of independent gene clusters encoding different ®mbriae and adhesins might be bene®cial in evading host immune response, or may allow multiple interactions with several different hosts during its complex life cycle.…”
mentioning
confidence: 84%
“…In ®ve cases the operons are¯anked by genes encoding transposases or integrases, again implying horizontal acquisition. Such high redundancy of ®mbria-related genes is also found in other bacterial pathogens, including Escherichia coli and Salmonella enterica serovar Typhi 17 . A large arsenal of independent gene clusters encoding different ®mbriae and adhesins might be bene®cial in evading host immune response, or may allow multiple interactions with several different hosts during its complex life cycle.…”
mentioning
confidence: 84%
“…2 and Tables 2 and 4). Moreover, 21 additional PAPI-1 ORFs show similarity with ORFs from only one of these pathogenicity islands, 14 with S. enterica (RL052, 72, 77-79, 81-85) and 7 with X. axonopodis (RL020, 35,[63][64][65]67). This abundant array of putative pathogenicity-related genes likely plays a role in the broad host range of PA14.…”
Section: Papi-1 Is a Pathogenicity Islandmentioning
confidence: 99%
“…For pathogenic Salmonella spp., genome sequencing efforts have identified over 15 distinct fimbrial types (Salmonella enterica serovars Typhimurium [42], Typhi [44], and Paratyphi [41]). Pioneering work by Baumler et al (5) and subsequent genomic comparisons (14,45,61) revealed that most fimbrial operons have a scattered distribution throughout the salmonellae. Early hypotheses that fimbriae were involved in adherence to host cells suggested that numerous fimbrial types would contribute to the host specificities and tissue tropisms of different Salmonella spp.…”
mentioning
confidence: 99%
“…However, despite much research, the role of fimbriae in the pathogenesis of Salmonella is still not well understood. In addition, no clear links have been made connecting one fimbrial type to a particular animal host or disease process (61).…”
mentioning
confidence: 99%